2018
DOI: 10.1371/journal.pone.0208143
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived occupational stress and psychological well-being among secondary school heads in Khyber Pakhtunkhwa, Pakistan

Abstract: The purpose of the study was to examine the relationship between perceived occupational stress and psychological well-being among secondary school heads in Khyber Pakhtunkhwa. A sample of 402 secondary school heads (male n = 260, female n = 142) was selected through multistage sampling technique. A descriptive, quantitative and correlative research design was used. For gathering information from the participants, two standardized tools i.e., “Occupational Stress Index (OSI)” and “Ryff’s Psychological Wellbeing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 36 publications
5
48
0
5
Order By: Relevance
“…The scale has 12 subscales that measure role overload (6 items), Role ambiguity (4 items), role conflict (5 items), unreasonable group and political pressure (4 items), responsibility for persons (3 items), under-participation (4 items), powerlessness (3 items), poor peer relations (4 items), intrinsic impoverishment (4 items), low status (3 items), strenuous working condition (4 items) and unprofitability (2 items). Suleman, Hussain, Shehzad, Syed, and Raja [ 51 ] found a reliability coefficient of 0.937 and 0.90 for OSI, using a split-half (odd-even) strategy and Cronbach Alpha respectively. Furthermore, for the purpose of this, we found a reliability index of 0,91 for the scale in Nigeria using Cronbach Alpha.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale has 12 subscales that measure role overload (6 items), Role ambiguity (4 items), role conflict (5 items), unreasonable group and political pressure (4 items), responsibility for persons (3 items), under-participation (4 items), powerlessness (3 items), poor peer relations (4 items), intrinsic impoverishment (4 items), low status (3 items), strenuous working condition (4 items) and unprofitability (2 items). Suleman, Hussain, Shehzad, Syed, and Raja [ 51 ] found a reliability coefficient of 0.937 and 0.90 for OSI, using a split-half (odd-even) strategy and Cronbach Alpha respectively. Furthermore, for the purpose of this, we found a reliability index of 0,91 for the scale in Nigeria using Cronbach Alpha.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the ABCDE model in explaining the relationships existing between activating (A) events associated with teaching children with ASD, dysfunctional thoughts, beliefs or cognitions arising from those events (B); the emotional and behavioural consequences of the beliefs (C). [ 51 , 52 ] Based on the foregoing, an activating event (A) in the context of the present study could be a challenging situation associated with either teaching and handling behavioural problems of CWA, teachers’ personal experiences, or work experiences; the belief (B) is the interpretation and cognitive imagery formed due to “A”. Such cognition about the event (B) elicits a consequence/effect (C) for the teacher, which may be adaptive or maladaptive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies demonstrated that occupational stress is a significant predictor of anxiety [29][30][31]. Furthermore, it inversely correlated with psychological well-being [32] and positively associated with depressive symptoms [13,33]. Nakao [34] recognized that occupational stress is a meaningful cause for mental health all over the world.…”
Section: Occupational Stress and Mental Healthmentioning
confidence: 99%
“…When employees perceive certain situations positively, it enhances their PWB and vice versa. Studies described that psychological wellbeing has a negative association with negative emotions that occurs due to a negative work environment or condition [133]. When employees perceive workplace events negatively, they experience anxiety, depression, and unpleasant emotions that, as a consequence, harm their psychological wellbeing.…”
Section: Perceived Organizational Politics Negative Affectivity Andmentioning
confidence: 99%